An efficient attribute-based encryption scheme based on SM9 encryption algorithm for dispatching and control cloud - Honghan Ji; Hongjie Zhang; Lisong Shao; Debiao He; Min Luo (Connection Science)
Dispatching and Control Cloud (DCC) is a cloud platform constructed by State Grid Corporation with the technology of cloud computing. DCC has improved the overall operation and monitoring capabilities, the smart level and many other advantages of power grid. However, the development of DCC has been hampered by security and privacy issues. Secure unified identity authentication, access control and authorisation management are significant topics in DCC. To find out a solution for the topics above, we have employed some encryption schemes using the attribute-based encryption(ABE), as ABE can preserve users' privacy and achieve access control with fine grain over the encrypted information. SM9 is a kind of Chinese official standard in the field of cryptography, which contains the SM9 encryption algorithm (SM9-IBE). In this paper, an ABE scheme based on SM9-IBE is proposed, making SM9 support fine-grained access control which would be better applied in DCC. Our proposed scheme (SM9-ABE) has been proven to be of great security in the selective CPA model under DBDH assumption. Furthermore, we implement SM9-ABE and evaluate its practical performance. The implementation indicates our scheme performs well in the matter of security and functionality, at an additional time cost which is acceptable.